2020
DOI: 10.1021/acs.nanolett.9b04094
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Immunogenic Cell Death Mediated by Intracellular Delivery of STING Agonist Nanoshells Enhances Anticancer Chemo-immunotherapy

Abstract: Many favorable anticancer treatments owe their success to the induction immunogenic cell death (ICD) in cancer cells, which results in the release of endogenous danger signals along with tumor antigens for effective priming of anticancer immunity. We describe a strategy to artificially induce ICD by delivering the agonist of stimulator of interferon genes (STING) into tumor cells using hollow polymeric nanoshells. Following intracellular delivery of exogenous adjuvant, subsequent cytotoxic treatment creates im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 51 publications
(72 reference statements)
3
58
0
Order By: Relevance
“…Although irinotecan is not a confirmed immunogenic cell death (ICD) inducer, it has been reported that irinotecan treatment increased the release of high-mobility group box1 protein (HMGB1), which is one of the important events of ICD. Previous report shows that irinotecantreated tumor cell supernatant (36) and cellular debris (37) promoted the maturation of cocultured DCs (up-regulated surface expression of CD80 and CD86), which is consistent with our in vivo data that PS3D1 alone elicited a modest DC maturation. However, irinotecantreated cellular debris failed to induce DC expression of IFN-, an essential ICD-associated primary signal for T cell cross-priming (37), which is consistent with our in vivo data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although irinotecan is not a confirmed immunogenic cell death (ICD) inducer, it has been reported that irinotecan treatment increased the release of high-mobility group box1 protein (HMGB1), which is one of the important events of ICD. Previous report shows that irinotecantreated tumor cell supernatant (36) and cellular debris (37) promoted the maturation of cocultured DCs (up-regulated surface expression of CD80 and CD86), which is consistent with our in vivo data that PS3D1 alone elicited a modest DC maturation. However, irinotecantreated cellular debris failed to induce DC expression of IFN-, an essential ICD-associated primary signal for T cell cross-priming (37), which is consistent with our in vivo data.…”
Section: Discussionsupporting
confidence: 93%
“…Previous report shows that irinotecantreated tumor cell supernatant (36) and cellular debris (37) promoted the maturation of cocultured DCs (up-regulated surface expression of CD80 and CD86), which is consistent with our in vivo data that PS3D1 alone elicited a modest DC maturation. However, irinotecantreated cellular debris failed to induce DC expression of IFN-, an essential ICD-associated primary signal for T cell cross-priming (37), which is consistent with our in vivo data. In addition, PS3D1-driven stimulation of DCs was insufficient for eliciting strong DC migration to the tdLNs for antigen cross-presentation and antigen-specific T cell cross-priming.…”
Section: Discussionsupporting
confidence: 93%
“…Cancer immunotherapies that stimulate the inherent immunological systems of the body to recognize, attack, and eradicate tumour cells have demonstrated varying degrees of success 1 5 . Recent studies revealed that immunogenic cell death (ICD) elicited by specific chemotherapy or radiotherapy makes the dead cell corpses ‘visible’ to dendritic cells (DCs) that present antigens to T cells with specific antitumour immune responses, which then control residual tumour cells 6 9 . However, ICD induced immune response can be severely weakened and even abolished by elevated reactive oxygen species (ROS) in the tumour microenvironment (TME) 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent publication, Chattopadhyay et al. 200 described the development of hollow polymeric nanoshells using PLGA to encapsulate STING for intracellular delivery. This resulted in synthetic immunogenic cell death (sICD) of cancer cells in three mouse tumor models.…”
Section: Targeting the Immunological Microenvironmentmentioning
confidence: 99%